Evaluasi Pengujian Kekerasan Material Aisi 4140 Menggunakan Full Factorial Design Of Experiment - Weriono Weriono; Rinaldi Rinaldi; Sepfitrah Sepfitrah (Fakultas Teknik UMSU, 2020)
Experiment is looking at the influence of dimensions, heat treatment temperature and cooling media effect linearly on hardness, tensile strength steel AISI 4140 so that the level comparison of the hardness of influence on the diameter variation (input effects the response). The Full Factorial Design of Experiment Method is used to assess the results of the hardness test in accordance with the testing hypothesis. Design of Experiment (DOE) has been widely used to determine design factors that significantly influence target responses and build empirical models that represent relationships between significant factors. Reviewing the literature revealed that the majority of researchers explored various DOE. Response Tempering heat treatment with Quenching Oil media, this study used AISI 4140 material with a diameter of 29 mm, 33 mm and 35 mm. Results AISI 4140 of commercial production by partial cutting are then taken for hardness testing. The Full Factorial Design of Experiment Method is used to assess the results of the hardness test in accordance with the hypothesis according to the analysis of variance(Anova). The response of the hardness test data input in the 300 & 900 direction is not influenced by the AISI 4140 material dimensions and the direction of the test surface data retrieval. Fo, 5%, 2.15 = 3.68, then Fo = 50.11> 3.68 in the 300 test direction and Fo, 5%, 2.15 = 3.68, then Fo = 70.79> 3, 68, in the 900 test direction where H0 cannot be accepted while H1 is accepted.